Pelaksanaan Elemen Numerasi Awal Dalam Aktiviti Bimbingan Oleh Ibu Bapa - Harun, Jamilah (2021)
Numeracy achivement in early childhood is vital as the basis for future achievement of numeracy. Previous studies have shown that parental involvement in various guidance activities at home affects the level of numeracy achievement of children even though they have not yet received any formal education in school. However, there are still less studies conducted to explore the appplication of numeracy elements during guidance activities carried out by parents, especially for preschool children. This qualitative study was conducted to explore the practice of application the elements of early numeracy through guidance activities by parents to preschool children. Specifically, this study explored the types of guidance activities carried out, the numeracy elements involved and the strategies used during the guidance activities. The study also explored the factors influencing parental practices related to early numeracy guidance activities. This case study involved two participants selected according to the purposive sampling method. They are two mothers who have preschool children. Data were obtained from videos of guidance activities between the mother and the child, interviews with mothers and reflection notes by mothers. Findings show that mothers were involved in various numeracy guidance activities at home either directly or indirectly. The findings also show that various numeracy elements were involved during the guidance activities, especially the elements of content, disposition, tools and context.